The research museum – a place of integrated knowledge production - Helmuth Trischler (Science Museum Group Journal)
Natural history museums have a longstanding history as sites of vital research based on their enormously rich collections, dating back to the late nineteenth century. Today they mostly position themselves as institutions of biodiversity research with their scientific programmes centre-stage and their public galleries as secondary activity. In contrast, museums of science and technology have long been struggling with their role in advancing the production and dissemination of knowledge based on object-oriented research. In his position as Head of Research at the Deutsches Museum, Germany’s leading museum of science and technology, from 1993 until his retirement in 2024, the author of this article has advocated for the inextricable integration of the fields of research, research infrastructure, and public mediation and communication. He has continuously sought to explore new avenues for realising the vision of the ‘integrated research museum’ that connects these three fields as closely as possible. In this article, he discusses the add-on value of integrating research into museums at various levels.